99mTc-MDP Bone Scan and 18F-FDG PET/CT Imaging of Multiple Extraskeletal Osteosarcomas. (November 2018) - Sun, Zhen-Kui; Shen, Chen-Tian; Qiu, Zhong-Ling; Luo, Quan-Yong
Abstract : Abstract: Extraskeletal osteosarcomas are uncommon entities in clinical practice, which account for 1% to 2% of all soft tissue sarcomas. We here reported a case of multiple extraskeletal osteosarcomas and nuclear medicine imaging findings of this disease in 99m Tc-MDP bone scan as well as 18 F-FDG PET/CT.